Factors Related to Psychological Distress among Primary Family Caregivers of Patients with Schizophrenia - Yulyani, Yulyani; Fitri, Nurwijaya; Mardiana, Nova (Genius Journal, 2026)
Objective: Mental health is a condition in which a person is cognitively, affectively, physiologically, behaviorally and socially healthy so that they are able to fulfill their responsibilities, function effectively in their environment and are satisfied with their role as individuals and in interpersonal relationships. The purpose of this study was to determine the relationship between social support, length of care and education on Psychological Distress in Primary Family Caregivers of schizophrenia patients at the Mental Health Polyclinic of Junjung Besaoh Hospital, South Bangka Regency in 2025. Method: The design in this study used cross-sectional with independent variables (social support, length of care and education) and dependent variables (Psychological Distress of Primary Family Caregivers). The population size in this study was 134 people and a sample of 63 people calculated using simple random sampling. The time of the study was May 14, 2025. Result: The results of the study using the Chi Square statistical test obtained a p-value for the social support variable of 0.000 <0.05, length of care 0.000 <0.000 and education 0.000 <0.05. This shows that there is a significant relationship between social support, length of care and education on Psychological Distress in Primary Family Caregivers of schizophrenia patients at the Mental Health Polyclinic of Junjung Besaoh Hospital, South Bangka Regency in 2025. Conclusion: Suggestions in this study are expected to be used as a source of reference and provide ideas for nursing students when practicing in the field so that students know the factors that can influence psychological distress, especially in primary family caregivers of schizophrenia clients.